Alcohol marketing versus public health: David and Goliath? - Mary Madden; Jim McCambridge (BMC, 2021)
Abstract Background Alcohol harms are rising globally, and alcohol policies, where they exist, are weak or under-developed. Limited progress has been made since the formulation of the World Health Organisation (WHO) Global Strategy in 2010. WHO is seeking to accelerate progress in implementing international efforts to reduce the harmful use of alcohol. The threat to global health posed by tobacco is well understood by policy communities and populations globally; by contrast alcohol is much less so, despite available evidence. The competition for epistemic authority Global alcohol corporations have sought to become trusted sources of advice for policy makers and consumers, while continuing to grow their markets. Evidence-informed public health messaging faces formidable competition from transnational corporations as the worlds of corporate and political communications, social and mainstream media become increasingly linked, presenting new opportunities for corporate actors to shape global health governance. Alcohol messaging that uses means of persuasion tied to industry agendas does not tell a clear story about commercial determinants of health, and does not contribute to health improvement. On the contrary, the basic tenets of an evidence-informed population-based approach are denied and the policy measures supported by high quality evidence are being opposed, because they are inimical to commercial interests. A David and Goliath metaphor for this state of affairs, which seems to fit at first glance, may unwittingly reinforce the status quo. Conclusion Public opinion on alcohol and policy issues varies across time and place and can be influenced by dedicated public health interventions. Alcohol marketing dominates people's thinking about alcohol because we currently allow this to happen. Greater ambition is needed in developing countermarketing and other interventions to promote evidence-informed ideas with the public. Alcohol policies need to be further developed, and implemented more widely, in order to arrest the growing burden of alcohol harms across the world.